Cardiac resynchronization therapy in heart failure patients by using left bundle branch pacing - Gu, Ying; Li, Yanming; Zhu, Ying; Lin, Xiuyu; Tian, Tian; Zhang, Qigao; Gong, Jianbin; Wang, Lei; Li, Jianhua (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Left bundle branch pacing (LBBP) is emerging as an effective alternative to achieve cardiac resynchronization therapy (CRT) and improve heart function. The purpose of our study was to investigate the feasibility and efficacy of LBBP in heart failure patients with left ventricular ejection fraction (LVEF) < 50% and left bundle branch block (LBBB). Methods All patients with complete LBBB and LVEF < 50% were retrospectively included in the study from April 2018 to April 2021 and underwent cardiac resynchronization therapy (CRT) via LBBP implantation. ECG, pacing parameters, NYHA functional class, echocardiographic measurements and complications were recorded and analyzed at implant, and during follow-up of 1, 6, and 12 months. Results LBBP was successful in all 34 patients (mean age 65.6±11.2 years, 67.6% men). A significant decrease in QRSd was observed after LBBP operation for 1 month (153.2±1.7ms vs. 111.9±2.6ms, P <0.01). LBB capture threshold and R-wave amplitude remained stable at 12-month follow-up compared with implantation values (0.62±0.13V@0.4ms vs. 0.73±0.21V@0.4ms, 12.02±5.68mV vs. 8.58±4.09mV, respectively). LVEF increased significantly (35.28 ±1.70% vs. 51.09±1.71%, P < 0.01) accompanied with reduced LVEDd (65.3±1.99mm vs. 53.58±2.07mm, P < 0.01) and LAD (49.03±1.32mm vs. 40.67±1.58mm, P < 0.01). Normalized LVEF (LVEF ≥ 50%) was found in 70.5% of patients at 12 months. NYHA classification, BNP and 6MWT were significantly improved at follow up of 12 months (all P < 0.01 vs. baseline). No deaths or heart failure hospitalizations were observed during follow up period. Conclusion The current work suggested that LBBP was feasible with high success implantation rate and effective to correct LBBB and improved left ventricular structure and function with low and stable pacing threshold.